A clinical assessment of antiretroviral-treated patients referred from the private sector to the South African government antiretroviral (ARV) programme: A retrospective analysis - Rianna Gounden (AOSIS, 2011)
A clinical assessment of antiretroviral-treated patients referred from the private sector to the South African government antiretroviral (ARV) programme: A retrospective analysis